Synthesis and Evaluation of PCL/Chitosan/CQD‐Fe Magnetic Nanocomposite for Wound Healing: Emphasis on Gene Expression - Elham Maghareh Abed; Fatemeh Yazdian; Abbas Akhavan Sepahi; Behnam Rasekh (Engineering in Life Sciences)
ABSTRACT The development of an effective and rapid method for healing the skin is of crucial importance. In this study, we prepared a porous scaffold made of polycaprolactone (PCL) and carbon quantum dots (CQDs), Fe, and Chitosan (Cs) as the scaffold core to cover the skin. Then evaluated antibacterial, biocompatibility, and wound healing properties as well as the expression of genes effective in wound healing. The PCL/Cs/CQD‐Fe scaffold was synthesized via electrospinning and was evaluated of morphology, functional groups, and structure through Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), and x‐ray diffraction (XRD). The viability of the L929 fibroblast stem cells was obtained. The antibacterial effect, biocompatibility, and wound healing efficiency of the scaffold were investigated through minimum inhibitory concentration (MIC), (3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT), and tissue analysis. The relative expression of genes platelet‐derived growth factor (PDGF), transforming growth factor beta (TGF‐β), and matrix metalloproteinase‐1 (MMP1) was assessed through RT‐PCR. The results of SEM showed the successful integration of the PCL scaffold with CQD‐Fe and Cs. The mean size of PCL/Cs/CQD‐Fe nanocomposite was in the range of 0.135–32.6 nm. The results of FTIR showed the formation of a link between CQD nanoparticles and Fe. The vibrating‐sample magnetometer (VSM) proved the super para magnetism of the CQD‐Fe magnetic nanoparticles (0.38 emu/g). The MIC of Cs/CQD‐Fe against Staphylococcus aureus and Escherichia coli bacteria was 0.08 and 0.04 µg/mL, respectively. The mean expression of genes TGF‐β and PDGF in the nanocomposite group were 0.05 and 0.015 on day 5 and 0.18 and 0.34 on day 15 and significantly increased after 15 days, whereas the mean expression of MMP1 in the nanocomposite group was 0.63 on day 5 and 0.12 on day 15 and significantly decreased after 15 days. According to the histological analysis, the thickest layer on Day 15 pertained to the nanocomposite group. Our findings indicated that PCL/Cs/CQD‐Fe can improve skin regeneration due to its antibacterial effect, biocompatibility, and non‐toxicity. This biocompatible nanocomposite is a scaffold that can be used for covering the skin.